2016
DOI: 10.1177/1533034615598622
|View full text |Cite
|
Sign up to set email alerts
|

Raman Spectroscopy of Experimental Oral Carcinogenesis

Abstract: Oral cancers suffer from poor 5-year survival rates, owing to late detection of the disease. Current diagnostic/screening tools need to be upgraded in view of disadvantages like invasiveness, tedious sample preparation, long output times, and interobserver variances. Raman spectroscopy has been shown to identify many disease conditions, including oral cancers, from healthy conditions. Further studies in exploring sequential changes in oral carcinogenesis are warranted. In this Raman spectroscopy study, sequent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
8
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 24 publications
(11 citation statements)
references
References 44 publications
3
8
0
Order By: Relevance
“…Similar trend in classification has also been stated by Kumar et al, wherein ex vivo and in vivo RS studies on epithelial HBP tissue were performed. [ 28,29 ]…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Similar trend in classification has also been stated by Kumar et al, wherein ex vivo and in vivo RS studies on epithelial HBP tissue were performed. [ 28,29 ]…”
Section: Resultsmentioning
confidence: 99%
“…[26,27] Previous RS studies from our laboratory have investigated experimental oral carcinogenesis in the HBP model using ex vivo, in vivo sequential and in vivo follow-up approaches. [28][29][30] Findings of the study demonstrated the efficacy of RS in identification of sequential biochemical changes occurring in HBP tissues. [28,29] The current study aims to identify the early events occurring during sequential oral carcinogenesis using hamster serum samples.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…PCA presented a minor overlap between three clusters, indicating a large difference between three cell lines. Furthermore, Kumar et al explored the change in differentiation efficacy during the cancer-inducing process, and the accuracy of cancer identification increased during the first 7 weeks, remained steady from 8 to 11 weeks, and exceeded 80% by the 14th week (Kumar et al, 2016).…”
Section: Diagnosis and Classification Of Oral Cancermentioning
confidence: 99%
“…Heber et al evaluated five protocols of carcinogenesis based on different number of weeks of carcinogen application to hamsters and the 6-week carcinogenesis protocol was selected for long-term studies of therapeutic effects (33). Furthermore, for the detection of oral carcinogenesis in early stages, Raman spectroscopy method was used to evaluate the levels of lipids, proteins and nucleic acids in early and late stages of oral carcinogenesis (34). Another way to detect the transformation of normal epithelium to pre-cancerous and cancerous states in early stages is non-linear optical microscopy for direct characterization of the epithelial-connective tissue interface (35).…”
Section: Articles Citing the Foundation Report On The Hamster Model Omentioning
confidence: 99%